Pengembangan Budaya Religius Melalui Manajemen Kurikulum di SMK Darussalam Blokagung 2 - Zulvan Maulana; Bahrudin Yusuf; M. Lutfi Munir; Septian Khoirul Umam (STIKes Ibnu Sina Ajibarang, 2024)
Curriculum management is important in education. Curriculum management carried out optimally will achieve educational goals, namely forming good behavior and personality in students. One way to shape this behavior and personality is by implementing a religious culture at school. This research aims to describe the development of religious culture through curriculum management at SMK Darussalam Blokagung 2. This research uses qualitative research with a phenomenological approach. Data collection techniques using interviews, observation and documentation. Data analysis techniques use data reduction, data presentation, and drawing conclusions. Data validity testing techniques use triangulation of sources and techniques. The results of this research show that the development of religious culture through curriculum management at SMK Darussalam Blokagung 2 is as follows: In the planning stage, the school holds a meeting at the beginning of each new school year which is attended by the principal, teachers and school committee. This process begins with determining the vision, mission and goals of SMK Darussalam Blokagung 2, then identifying needs and adapting to existing conditions in society, then the school can implement religious culture in learning and school habituation activities which are carried out in daily, weekly and annual activities. The stage of organizing the development of religious culture is that the school principal is responsible for coordinating with teachers and the school committee to carry out activities in accordance with their duties and fields. At the curriculum implementation stage, the development of religious culture is carried out by carrying out habituation and learning activities. At the evaluation stage at the end of each semester, we evaluate the material, approaches, strategies and assessments both in habituation activities and in learning. The curriculum evaluation is based on the results of learning evaluation and supervision carried out reflectively, namely, daily evaluation, evaluation per learning unit, evaluation per semester, and evaluation per year.